A multicenter, randomized, double-blind trial comparing the efficacy and safety of TUDCA and UDCA in Chinese patients with primary biliary cholangitis. Issue 47 (November 2016) - Ma, Hong; Zeng, Minde; Han, Ying; Yan, Huiping; Tang, Hong; Sheng, Jifang; Hu, Heping; Cheng, Liufang; Xie, Qing; Zhu, Youfu; Chen, Guofeng; Gao, Zhiliang; et al.
Abstract: Aim: Tauroursodeoxycholic acid (TUDCA) is a taurine conjugated form of ursodeoxycholic acid (UDCA) with higher hydrophility. To further evaluate the efficacy and safety of TUDCA for primary biliary cholangitis (PBC), we performed this study on Chinese patients. Methods: 199 PBC patients were randomly assigned to either 250 mg TUDCA plus UDCA placebo or 250 mg UDCA plus TUDCA placebo, 3 times per day for 24 weeks. The primary endpoint was defined as percentage of patients achieving serum alkaline phosphatase (ALP) reduction of more than 25% from baseline. Results: At week 24, 75.97% of patients in the TUDCA group and 80.88% of patients in the UDCA group achieved a serum ALP reduction of more than 25% from baseline ( P  = 0.453). The percentage of patients with serum ALP levels declined more than 40% following 24 weeks of treatment was 55.81% in the TUDCA group and 52.94% in the UDCA group ( P  = 0.699). Both groups showed similar improvement in serum levels of ALP, aspartate aminotransferase, and total bilirubin ( P  > 0.05). The proportion of patients with pruritus/scratch increased from 1.43% to 10.00% in UDCA group, while there's no change in TUDCA group ( P  = 0.023). Both drugs were well tolerated, with comparable adverse event rates between the 2 groups. Conclusions: TUDCA is safe and as efficacious as UDCA for the treatment of PBC, and may be better to relieve symptoms than UDCA. Abstract : Supplemental Digital Content is available in the text